Evaluation of the Diuretic Activity of Aqueous and 80% Methanol Extracts of Croton macrostachyus(Euphorbiaceae) Leaves in Saline-Loaded Rats - Tufer S; Engidawork E; Ayele AG; Bashea C (Dove Medical Press, 2021)
Sara Tufer,1 Ephrem Engidawork,1 Akeberegn Gorems Ayele,1 Chala Bashea2 1Department of Pharmacology and Clinical Pharmacy, School of Pharmacy, College of Health Science, Addis Ababa University, Addis Ababa, Ethiopia; 2Department of Medical Laboratory Sciences, College of Health Sciences, Addis Ababa University, Addis Ababa, EthiopiaCorrespondence: Akeberegn Gorems AyeleDepartment of Pharmacology and Clinical Pharmacy, School of Pharmacy, College of Health Sciences, Addis Ababa University, Zambia Street, PO Box 9086, Addis Ababa, EthiopiaTel +251-98-540-8322Email Akeberegn.gorems@aau.edu.etBackground: Croton macrostachyus (Euphorbiaceae) extract is a folk medicine traditionally used for treating a number of disorders, including edematous conditions. The present study aimed to evaluate the diuretic effects of aqueous and 80% methanol leaf extracts of Croton macrostachyus in saline-loaded rats.Methods: Rats of either sex were randomly assigned into eight groups of eight animals per group. The animals were treated with vehicle (distilled water), standard (furosemide 10 mg/kg), and three doses (100, 200, and 400 mg/kg) of aqueous and 80% methanol leaf extracts after loading of normal saline (15 mL/kg). Then, urine volume, electrolyte concentration, and pH were measured as parameters of evaluation. Concentrations of urinary Na+ K+, and Cl– were determined and Na+:K+ and Cl−:Na+ + K+ ratios calculated to reveal possible mechanisms.Results: The aqueous extract at 200 mg/kg had produced significant diuresis by hour 3, while the same dose of 80% methanol extract had produced substantial diuresis by the end of hour 4. Both extracts at 400 mg/kg produced significant diuresis from hour 2 to hour 5. In terms of effect on electrolysis, 400 mg/kg aqueous extract produced significant natriuresis, and a kaliuresis effect was observed for both extracts at higher doses and 200 mg/kg aqueous extract.Conclusion: The findings collectively indicated that both aqueous and 80% methanol extract showed significant diuretic activity, thereby justifying the plant’s traditional use as a diuretic agent.Keywords: Croton macrostachyus, diuretic activity, electrolyte, leaf, rats